The Predictive Role of Chinese EFL Teachers’ Individual Self-Efficacy and Collective Efficacy in Their Work Engagement - Yang, Jianbo (Frontiers in Psychology, 2021)
Both teacher individual self-efficacy (TSE) and collective efficacy (TCE) are indispensable since they impact the amount to which teachers are engaged in their work. Although several studies have been carried out considering the referred points, it seems to be a must to conduct such studies among Chinese teachers to measure the link between these three variables. In this study, the author has made endeavors to scrutinize the interplay among TSE, TCE, and work engagement (WE), and also the significant role of self-efficacy and collective efficacy in WE. Participants were 346 university professors and middle school teachers, from 25 provinces of China. Results substantiate that TSE and TCE predict teachers’ WE. In other words, the more efficacious a teacher is, the more he is engaged in his work. In the discussion part, the consistency between the current study and some other studies with the same topic is unpacked. Then, some limitations are discussed and further implications are suggested.